Wouldn't you rather be happy than be rich? - Abd Razak, Dzulkifli (2009)
IT is that time again when it is customary to wish everyone a Happy New Year! The operational word is, of course, "Happy"! But it may not be so for this year, if what have been forecast for 2009 is to be believed. Many pundits have predicted that the worst is in store with unemployment on the rise as more companies fold up. The stock market is predicted to be on the decline with extreme volatility. Recession and depression have not been completely ruled out. Bailouts, even nationalisations, will continue, and the global confidence in the US currency will stay low.